Composite Anion-Exchange Membrane Fabricated by UV Cross-Linking Vinyl Imidazolium Poly(Phenylene Oxide) with Polyacrylamides and Their Testing for Use in Redox Flow Batteries - Martyna Charyton; Cristina Iojoiu; Peter Fischer; Gerard Henrion; Mathieu Etienne; Mateusz L. Donten (Membranes, 2021)
Composite anion-exchange membranes (AEMs) consisting of a porous substrate and a vinyl imidazolium poly(phenylene oxide) (VIMPPO)/acrylamide copolymer layer were fabricated in a straightforward process, for use in redox flow batteries. The porous substrate was coated with a mixture of VIMPPO and acrylamide monomers, then subsequently exposed to UV irradiation, in order to obtain a radically cured ion-exchange coating. Combining VIMPPO with low-value reagents allowed to significantly reduce the amount of synthesized ionomer used to fabricate the mem- brane down to 15%. Varying the VIMPPO content also allowed tuning the ionic transport properties of the resulting AEM. A series of membranes with different VIMPPO/acrylamides ratios were prepared to assess the optimal composition by studying the changes of membranes properties—water uptake, area resistivity, permeability, and chemical stability. Characterization of the membranes was followed by cycling experiments in a vanadium RFB (VRFB) cell. Among three composite membranes, the one with VIMPPO 15% w/w—reached the highest energy efficiency (75.1%) matching the performance of commercial ion-exchange membranes (IEMs) used in VRFBs (Nafion® N 115: 75.0% and Fumasep® FAP 450: 73.0%). These results showed that the proposed composite AEM, fabricated in an industrially oriented process, could be considered to be a lower-cost alternative to the benchmarked IEMs.